THE ISLAMIC PERSPECTIVE OF NON-MUSLIM LEADERS IN INDONESIAN MUSLIM MAJORITY COMMUNITIES - Ali Abdul Wakhid; Mohd Shahril Bin Ahmad Razimi; Moh. Mukri; Is Susanto (Akademika : Jurnal Pemikiran Islam, 2021)
The leader is a key component of the government system. Referring to the Prophet Muhammad and his companions' leadership attributes as described in many literatures, a leader must be a Muslim who is istiqamah (consistent), trustworthy, honest, and fair. Another issue comes when the leader is not Muslim but has a trustworthy, honest, and fair character in carrying out his leadership responsibilities. This article tries to give answers to these issues through many sources of literature, particularly leadership for the Indonesian Muslim community, which has a Muslim population of 231.06 million (86.7 percent) (according to The Royal Islamic Strategic Studies Center/RISSC). According to the findings of this study, the leader serves as a substitute for the Prophet in world and state affairs. As a result, the legislation enabling non-Muslims to handle Muslim affairs is prohibited, because non-Muslim leaders will be unable to implement it for the Muslim community. His leadership will put his group's interests over the Muslim group's. Although scholars disagree in their opinions on non-Muslim leaders, some scholars restrict the selection of non-Muslim leaders since they share beliefs with helpers and leaders. Some other scholars agree that non-Muslim leaders can exist in Muslim-majority territories because they no longer fit the contemporary context.